A layered porous Ni structure contributes to superior low-temperature performance of hydrogen storage alloys. (13th January 2020) - Chen, Y.; Wen, Z.; Jia, J.H.; Yang, C.C.; Jiang, Q.
Abstract: The poor low-temperature performance of negative electrode materials— hydrogen storage alloys (HSAs) has impeded applications of nickel metal hydride batteries in new energy vehicles. Here, we propose a simple and effective strategy to improve low-temperature properties of the commercial HSA with HCl etching and heat treatment. The layered porous Ni surface structure formed during this process improves the electrochemical reaction kinetics, and thus results in a larger discharge capacity of 102.63 mAh g −1 at 233 K compared with those of bare (11.52 mAh g −1 ) and acid-corroded (43.00 mAh g −1 ) alloys. This method could be extended to enhance the low-temperature performance of other HSA systems. Graphical abstract: In this work, a simple and effective method has been proposed to improve the low-temperature performance of hydrogen storage alloys by forming a layered porous Ni structure on alloy surface via HCl etching and annealing, which shows large discharge capacity (102.63 mAh g −1 at 233 K) and excellent high rate dischargeability (96.97 mAh g −1 at 273 K at 1500 mA g −1 ) at low temperatures. Image 1 Highlights: A layered porous Ni structure was formed on hydrogen storage alloys surface. The fabrication strategy is facile and effective. The electrode shows enhanced low-temperature properties. The mechanisms behind enhanced electrochemical performance are revealed.